Synthesis of β-Cyclodextrin-Decorated Dendritic Compounds Based on EDTA Core: A New Class of PAMAM Dendrimer Analogs - Israel González-Méndez; Esteban Loera-Loera; Kendra Sorroza-Martínez; Mireille Vonlanthen; Fabián Cuétara-Guadarrama; María Josefa Bernad-Bernad; Ernesto Rivera; Jesús Gracia-Mora (MDPI AG, 2022)
In this work, two dendritic molecules containing an ethylenediaminetetraacetic acid (EDTA) core decorated with two and four β-cyclodextrin (βCD) units were synthesized and fully characterized. Copper(I)-catalyzed alkyne-azide cycloaddition (CuAAC) click chemistry under microwave irradiation was used to obtain the target compounds with yields up to 99%. The classical ethylenediamine (EDA) core present in PAMAM dendrimers was replaced by an EDTA core, obtaining platforms that increase the water solubility at least 80 times compared with native βCD. The synthetic methodology presented here represents a convenient alternative for the rapid and efficient construction of PAMAM analogs. These molecules are envisaged for future applications as drug carriers.